Testing Linear versus Logarithmic Regression Models: A Comment - Ericsson, Neil R. (Review of Economic Studies, 1982)
In a recent article, Aneuryn-Evans and Deaton propose asymptotic formulae for analysing Monte Carlo studies of the Cox statistics for testing non-nested hypotheses. This note shows the invalidity of those formulae by demonstrating that, in general, the Cox statistics do not have a singular joint asymptotic distribution.